Storytelling and Minecraft in Education: Creating a World and Measuring its Impact on the Learning Process - João Miguel Matos Monteiro (2022)
Ever since its full release in 2011, Minecraft has asserted itself as one of the most popular games with children around the world. Its sandbox features possibilities have not gone unnoticed by educators, with Minecraft Education Edition's release in 2016 and its over 600 available public lessons proving its value. Proceeding from Rinja and van der Jagt's assertion from 2004 that people tend to pay much more attention to what is told when the information is put into an interesting and exciting story, this research proposed a case study conducted with 10 classes from 3rd to 6th grades to analyse the utilization of Minecraft to assist the learning process, and measure the impact of incorporating storytelling and other game-based elements in it. Instead of employing a pre-built world as the object for the case study with the students, a new world was projected and constructed, in association with Visionarium and incorporating the Microsoft Safer Internet Day 2022 project, resulting in an engaging adventure though a Minecraft world capable of teaching children about internet safety. The results of this case study reassert the idea that Minecraft can be utilized in the classroom with great success at captivating and motivating children and, not negating the values that the sandbox features of the game provide, also introduces the idea that adding storytelling and other game-based elements to Minecraft can further assist the learning process.